Abundance and factors affecting the appearance of Siamese fireback and Red junglefowl in the lowland forest of Thailand - RONGLARP SUKMASUANG; PHRAEMAI CHAISOMBOON; PAANWARIS PAANSRI; YONGYUT TRISURAT; PEMIKA KANKA; NORASET KHIOWSREE; BUNYATHIPORN KAEWDEE; KITTIWARA SIRIPATTANUKUL; ANDAMAN CHANKHAO (Society for Indonesian Biodiversity, 2023)
Abstract. Sukmasuang R, Chaisomboon P, Paansri P, Trisurat Y, Kanka P, Khiowsree N, Kaewdee B, Siripattanukul K, Chankhao A. 2023. Abundance and factors affecting the appearance of Siamese fireback and Red junglefowl in the lowland forest of Thailand. Biodiversitas 24: 5718-5730. Pheasants are indeed important species in various ecosystems. Studies of the abundance and factors influencing the presence of pheasant species have been conducted in the lowland areas of the Khao Ang Rue Nai Wildlife Sanctuary, Thailand, using camera trapping and species distribution models. A total of 23 factors, 2 bio-physiological, 2 geophysical, and 19 climate factors, were used to analyze in this study. The study revealed the presence of only two species of pheasants in the surveyed area, namely the Siamese fireback (Lophura diardi) and the Red junglefowl (Gallus gallus). The encounter rates were calculated as 1.74 photos per 100 trap nights for the Siamese fireback and 2.28 photos per 100 trap nights for the Red junglefowl. The factors influencing the presence of both Siamese fireback and the Red junglefowl were climate factors followed by biophysical and topography factors, respectively. The study's results highlight the importance of climate factors to the appearance of the pheasants, even in lowland areas. The results showed that the both pheasants responded more positively to the secondary forests, the grassland followed by dry dipterocarp forest than to other forest types. Therefore, conservation efforts to protect the areas inside are crucial for conserving the species' population.